Opening boxes: religious education in school curriculum - Pozzer, Adecir (2018)
This paper presents the historical route of Religious Education in Brasil, since its incorporation as teaching of religion to the emergence of other perspectives that considered it as responsible for the study of knowledge and religious and non-religious knowledge without proselytism. First, we use the metaphor of the box to illustrate the experiences of opening and closing adopted by subjects who are in relation with differences and that which is different. In the second place, the paper presents how Religious Education became a box opener when allowing access to all kind of knowledge and knowledge produced by different cultures and religious traditions.